POLITIK DIPLOMASI PERDANA MENTERI AMIR SYARIFUDIN DAN PERJANJIAN RENVILLE - Ervani Ervani; Sumiyatun Sumiyatun; Kuswono Kuswono (Swarnadwipa, 2019)
In the early days of Indonesian independence, the Netherlands was a country that did not want to recognize Indonesia's de facto independence. Under Prime Minister Amir Syarifudin, Indonesia carried out political diplomacy with the Netherlands. Amir Syarifudin chose diplomacy because he saw that the Dutch fighting strength was much better than Indonesia at that time and so that there would be no morebloodshed. The purpose of writing this article is to find out how Indonesia's diplomacy politics during the revolution under Prime Minister Amir Syarifudin was an effort to defend Indonesia's independence. In this study, the author uses the historical method with data collection techniques using relevant literaturestudies. The results showed that the diplomacy chosen by Prime Minister Amir Syarifudin was still not able to satisfy the Indonesian people. The conclusion of this research is that Amir Syarifudin's diplomacy caused great disappointment and brought down Amir Syarifudin's cabinet.Keywords: Politics; Diplomacy; Amir Syarifudin